The influence of regional features on design museums - Hvan, Елена; Burkit, Акбота (Рroblems of engineering and professional education, 2023)
This article describes examples of regional features and their impact on design of museums. Vivid examples of architectural solutions have analyzed. On this basis, the basic conditions have established and developed, that influence the formation of regional architecture. However, these forming factors bring to adaptation of museums' architecture, which were conceiving in traditional atmosphere, at the same time, were slaving under all of the world's architectural flow.